The privatization of Argentine airports - Lipovich, Gustavo Andres (2008)
The significant increase in air traffic in Argentina during 1990s highlighted a need to upgrade the country’s airport infrastructure. In the ideological and political–economical context of the period, the heavy investment required could not be carried through without private capital and thus a National Airport System was developed with an accompanying regulatory agency. This article looks at the origin, characteristics, and operations of this system.